1980
DOI: 10.1177/036354658000800505
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of injuries in youth soccer

Abstract: Soccer has rapidly gained in interest in the United States. A paucity of available data on soccer injuries led us to formulate this study to quantitate and categorize injuries acquired during a program of youth soccer (under age 19). A prospective study of 1,272 players showed an injury rate of 2.6 injuries per 100 participants. The injury rate for girls was twice as great as for boys. The under 10-age group was seldom injured (less than 1 injury per 100 participants), but the overall injury rate in the player… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
73
3
3

Year Published

1988
1988
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(89 citation statements)
references
References 8 publications
10
73
3
3
Order By: Relevance
“…18 The paucity of research specifically related to Association Football is apparent as three studies were reported within this sport. 17 All of the available data used subjective assessments of pitch conditions reporting associations of 24% 19,20 and 21% 21 between pitches and injury. It is unclear whether subjective measures provide a true reflection of pitch hardness and linking them to injury is difficult.…”
Section: Current Evidence That Natural Turf Pitches Affect Injury Incmentioning
confidence: 99%
“…18 The paucity of research specifically related to Association Football is apparent as three studies were reported within this sport. 17 All of the available data used subjective assessments of pitch conditions reporting associations of 24% 19,20 and 21% 21 between pitches and injury. It is unclear whether subjective measures provide a true reflection of pitch hardness and linking them to injury is difficult.…”
Section: Current Evidence That Natural Turf Pitches Affect Injury Incmentioning
confidence: 99%
“…Of all injured players who wore shin guards, only 2.2% (1/45) sustained an injury to a leg. Of all players documented as not wearing shin guards at the time of injury, 10.5% (16/152) had leg injuries. On the basis of shin guard use reported among the injured players, excluding those with leg injuries, 24.4% of players wore some kind of shin guard.…”
Section: Incidence Of Injuriesmentioning
confidence: 99%
“…Soccer injuries have been reported to occur for the most part in the lower extremity in youth players (17,18), as is the case for professional (19) and senior players (20,21). The possible explanations for this are as follows: i) in soccer players, the lower extremity joints are subjected to severe mechanical stresses and are easily injured due to excessive and repetitive use of the joints; and ii) soccer players expose their lower extremity joints to repetitive intense impacts and torsional and/or axial loads.…”
Section: Discussionmentioning
confidence: 99%
“…This could be explained by the finding that relatively more sprains are localized in the ankle joint of soccer players (22). Furthermore, a substantial number of preceding studies have demonstrated that among all joint injuries occurring in soccer players the ankle sprain is the most common (17)(18)(19)(23)(24)(25)(26)(27)(28)(29). The results from the present study showed that the VAS scores for the 'pain on moving' subscale were substantially higher than the scores for the 'pain at rest' subscale and 'pain on pressing' at the ankle joint, as well as other lower extremity joints in youth soccer players.…”
Section: Discussionmentioning
confidence: 99%